THE STRATEGY OF THE WOMEN'S EMPOWERMENT, CHILD PROTECTION, AND FAMILY PLANNING OFFICE IN PREVENTING BULLYING IN BOJONEGORO REGENCY - Musta'ana; Cahyono, Teguh; Septiana, Vita Nugrah (Universitas Kadiri, 2025)
This study aims to analyze how the Strategy of the Office of Women's Empowerment, Child and Family Protection in Bullying Prevention in Bojonegoro Regency. This research was conducted using qualitative methods. Data collection techniques were carried out through literature studies and field studies, including observation, interviews, documentation studies, and triangulation. Determination of samples/informants in this study was conducted using purposive sampling of 5 people. While the data analysis procedure uses the Milles and Huberman data model. The final results of this study concluded that this program has good targets and positive output, but the implementation of socialization has not been optimal due to the lack of government commitment. Although there has been progress in handling bullying cases, obstacles such as slow resolution of cases and low community involvement still occur. It is recommended to expand the reach of socialization, strengthen the reporting system, improve the competence of professional staff, and develop HR capacity at DP3AKB Bojonegoro Regency.While the data analysis procedure uses the Milles and Huberman data model. The final results of this study concluded that this program has good targets and positive output, but the implementation of socialization has not been optimal due to the lack of government commitment. Although there has been progress in handling bullying cases, obstacles such as slow resolution of cases and low community involvement still occur. It is recommended to expand the reach of socialization, strengthen the reporting system, improve the competence of professional staff, and develop HR capacity at DP3AKB Bojonegoro Regency.